Orbital decompression. (11th March 2021) - Groombridge, Christopher; Maini, Amit; Mathew, Joseph; O'Keeffe, Francis; Noonan, Mike; Smit, De Villiers; Fitzgerald, Mark; Hall, Anthony
Abstract : A trauma patient with orbital compartment syndrome may lose vision within hours of the injury. This article describes an approach to decompressing the orbit which may be sight‐saving.